Bartonella Species Infection in Cats: ABCD guidelines on prevention and management. Issue 7 (July 2013) - Pennisi, Maria Grazia; Marsilio, Fulvio; Hartmann, Katrin; Lloret, Albert; Addie, Diane; Belák, Sándor; Boucraut-Baralon, Corine; Egberink, Herman; Frymus, Tadeusz; Gruffydd-Jones, Tim; Hosie, Margaret J; Lutz, Hans; et al.
Overview: Over 22 Bartonella species have been described in mammals, and Bartonella henselae is most common worldwide. Cats are the main reservoir for this bacterium. B henselae is the causative agent of cat scratch disease in man, a self-limiting regional lymphadenopathy, but also of other potentially fatal disorders in immunocompromised people. Infection: B henselae is naturally transmitted among cats by the flea Ctenocephalides felis felis, or by flea faeces. A cat scratch is the common mode of transmission of the organism to other animals, including humans. Blood transfusion also represents a risk. Disease signs: Most cats naturally infected by B henselae do not show clinical signs but cardiac (endocarditis, myocarditis) or ocular (uveitis) signs may be found in sporadic cases. B vinsonii subspecies berkhoffii infection has reportedly caused lameness in a cat affected by recurrent osteomyelitis and polyarthritis. Diagnosis: Isolation of the bacterium is the gold standard, but because of the high prevalence of infection in healthy cats in endemic areas, a positive culture (or polymerase chain reaction) is not confirmatory. Other compatible diagnoses must be ruled out and response to therapy gives a definitive diagnosis. Serology (IFAT or ELISA) is more useful for exclusion of the infection because of the low positive predictive value (39–46%) compared with the good negative predictive value (87–97%). Laboratory testing is required for blood donors. Disease management: Treatment is recommended in the rare cases where Bartonella actually causes disease.